Comparative Analysis of Secondary School Teachers’ Competency in Literacy and Numeracy: A Cross-National Evidence from Indonesia and Afghanistan - Takdir, Muh.; Listyasari, Winda Dewi; Rahmawati, Desi; Fadholi, Muhamad; Maheswari, Jenar; Febriani, Aisyah; Kayen, Hazrat Shah (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to analyze and compare the competencies of secondary school teachers in teaching literacy and numeracy in Indonesia and Afghanistan.Methods – Employing a descriptive comparative quantitative approach, the study involved 200 teachers from both countries selected through a stratified random sampling technique. Data were collected using questionnaires, classroom observations, and semi-structured interviews, and analyzed using descriptive statistics to compare the mean competency scores. Findings – The findings revealed that teachers in Indonesia demonstrated higher competency scores in literacy (71.4) and numeracy (68.3) compared to teachers in Afghanistan, who scored 62.8 in literacy and 59.7 in numeracy. Indonesian teachers also reported greater participation in professional training, more frequent use of educational technology, and a stronger application of contextual approaches in their teaching practices. The study underscores the importance of continuous professional development, resource support, and context-based pedagogical approaches in enhancing teacher competencies. Research Implications – These findings contribute to the formulation of more responsive educational policies and open avenues for further research within broader geographical and socio-cultural contexts.